Monomeric states of the beta-amyloid peptide investigated under high pressure by nuclear magnetic resonance spectroscopy - Cavini, Ítalo Augusto (2018)
The main histological feature of Alzheimer\'s disease is the presence of amyloid plaques in the patient\'s brain. The most abundant element of these plaques is the β-amyloid peptide (Aβ). Initially soluble, the peptide exhibits in solution an intricate equilibrium among monomeric, oligomeric (some of which are regarded as the toxic species) and fibrillar states, which prevents its crystallization and subsequent structural determination by X-ray diffraction. High-pressure nuclear magnetic resonance (NMR) spectroscopy has been used by our group to detect rare, high-energy monomeric Aβ (1-40) states, coexisting in equilibrium with oligomers and fibrils. This work aims to characterize the thermodynamics and the structure of the rare excited states of the Aβ peptide through the use of high pressure NMR. A large collection of NMR spectra of the Aβ (1-40) peptide as a function of pressure was recorded and analyzed. Secondary structure predictions revealed that the Aβ peptide adopts extended β-strand-like structures, similar to those found in amyloid-fibril structures. From the pressure curves of chemical shifts and cross-peak volumes, at least three monomeric states could be detected, which were thermodynamically characterized by the calculation of the variation of their Gibbs free energy (ΔGij) and molar partial volumes (ΔVij). The study of nuclear Overhauser effects (NOEs) and 3JHα-HN NMR couplings reinforces the existence of extended structures with β-strand propensity, both at ambient (0.1 MPa) and high (275 MPa) pressures. The interaction between the Aβ peptide and the D-peptides RD2 and RD2D3, D-enantiomeric fibril inhibitors, was also characterized. Our results indicate that the D-peptides recognize and bind to a more compact conformation of Aβ. The formation of the Aβ-D-peptide heterodimers ultimately prevents the formation of toxic oligomers, therefore representing a potential therapy against Alzheimer´s disease. Additionally, in the second chapter, we present results on the coiled-coils (CC) from group-III human septins (SEPT1, SEPT2, SEPT4 and SEPT5) also studied by NMR spectroscopy. Septins are GTP-binding proteins present in most eukaryotic organisms and capable of forming filaments, which are essential in cell division. In this study, we used 1H-1H-NOESY spectra to detect the orientation and helix pairings adopted by the C-terminal coiled-coils in solution. The NOE analysis, aided by back-calculated spectra, showed that the only sequence to show an antiparallel structure was SEPT2CC; all the others are parallel. However, the disappearance of specific peaks in the NMR spectrum of SEPT5CC caused by the attachment of a paramagnetic spin label indicates an antiparallel orientation, contrary to our other NMR result. A simple evaluation of the coiled-coil heptameric positions, based on the occurrence of each amino acid residue occupying each position, revealed that both orientations are equally stable. Despite being far less stable compared to other coiled-coils, both could exist physiologically. Other results from the group also suggest that these peptides could have the ability to form both parallel and antiparallel coiled-coils. We speculate that the antiparallel conformation might be related to cross-linking between filaments.